Electrophoretic studies of redfish (Genus sebastes) from Icelandic and Greenland waters - Nedreaas, Kjell Harald; Nævdal, Gunnar; Johansen, Torild (ICES, 1992)
Sebastes spp. from Icelandic and Greenland waters were analysed for biochemical genetic variation by agar gel and starch gel electrophoresis. The main emphasize was put on S. marinus, but the oceanic type S. mentella from the Irminger sea and S. viviparus from coastal Icelandic waters were studied for comparisons. The results were compared to earlier studies on material from East Greenland. Faroe Islands, British sector and off the Norwegian coast (Nedreaas and Nævdal 1991). The S. marinus samples were collected southwest of Iceland, on the southeast coast, north of Iceland and from both sides of Cape Farewell. S. viviparus were collected from five localities south of Iceland. Haemoglobin and three enzymes in liver and muscle tissue were analysed by use of agar gel and starch gel electrophoresis. Isocitrate dehydrogenase (IDH) were analysed because it shows polymorphism in liver tissue; malate dehydrogenase (MDH), malic enzyme (ME) and haemoglobins first of all because they are species specific. The oceanic type S. mentella showed no polymorphism in either of the enzymes and showed an overall picture identical to what has been found in this species in other areas. Idh-genotypes in the samples from Iceland S. marinus showed a similar distribution as found around Faroe Islands and the coast of Norway while the Greenland samples were deviating. Intersample differences were indicated also in S. viviparus. Pattern of MDH was diagnostic for S. viviparus. In all three species were found somewhat unclear variations that will be further studied., The haemoglobin patterns were monomorphic in all three species, and as found before, clearly diagnostic for S. mentella, while considerable variation were noted in the material of S. marinus from Greenland.